Comparison of Performance Analysis of Comodo SSL and Let's Encypt SSL (Case Study: Bukalapak and Tokopedia) - Joko Dwi Santoso (Hemispheres Press, 2022)
The world is becoming connected with the internet, the arrival of the internet has greatly influenced new network technology. The number of internet users is increasing day by day, there is an increase in online transactions. As a growing number of websites have sprung up with easy information transmission facilities, it has been seen that it has caused a huge increase in fraud. Broad e-commerce spectrum (B2B / B2C / C2C), banking, finicial trading and others. Business applications require very high data exchange for security. Secure Sockets Layer (SSL), and its influence on web server performance. Secure SocketLayer (SSL) is the most popular protocol used on the internet to facilitate communication security through authentication, encryption, and decryption. Although the use of SSL provides adequate security, this can cause a decrease in performance compared to insecure protocols as well as a decrease in the percentage of downloads compared to insecure protocols. In this paper, we analyze the performance and impact of SSL on web performance and the type of SSL used by Bukalapak e-commerce and Tokopedia